Sentiment analysis and gender differences in earnings conference calls - De Amicis, Chiara; Falconieri, Sonia; Tastan, Mesut (Journal of Corporate Finance, 2021)
We apply textual analysis to the transcripts of nearly 78,000 earnings conference calls between 2004 and 2018, comparing the difference in sentiment between female and male senior managers (CEOs and CFOs). We focus on two main measures of sentiment: tone and vagueness. Our contribution is twofold. Firstly, we show that female executives employ a more positive and less vague tone than their male colleagues during conference calls. The more positive and less vague tone of female executives does not reflect incremental information content but instead appears to be a linguistic feature that distinguishes female from male executives. Secondly, we find that financial analysts participating in conference calls exhibit a gender bias as they are less positive and more vague when facing a female executive. However, the stock market reaction to the call is affected by the sentiment of the call, but not by the executive's gender.